Classificação das alterações cromatínicas de espermatozoides bovinos e sua correlação com a eficiência na produção in vitro de embriões - Hiraiwa, Sara Hissae (2015)
Chromatin alterations, despite not being evaluated in the spermogram routine affect the fertility of bulls. The most used method of chromatin evaluation is the SCSA (Sperm Chromatin Structure Assay). However it is a high method cost. An alternative method is the toluidine blue (TB) after acid hydrolysis associated with computer analysis - this method is presented as an equivalent and affordable tool. In addition to its lower cost, this methodology measures the intensity of decondensation and heterogeneity chromatin. However, it has not yet determined which decondensation and heterogeneity levels interfere with bull fertility. This study aims to define which levels of decondensation and heterogeneity chromatin are acceptable in order not to prejudice the bull fertility and the embryonic development. It also aims to propose a classification of cattle sperm chromatin alteration according to their location, and it also aims to verify if each type of alteration influences the process of fertilization and the early embryonic development. To this, animals semen samples induced to subfertile were used for in vitro production of embryos (IVP). These samples were evaluated using the AT method, and computer analysis. To characterize the semen fertility samples, cleavage ratio were evaluated on the second day and morphologically normal blastocysts in the seventh day of each IVF. With the use of computer image analysis it was possible to make the following classification of chromatin alterations: decondensation of the base of the head (DB), in the basal half (DBH), in scattered areas (SA), in the central axis of the head (DCA) and the entire length of the head (DT). It was used the estimation of Pearson (p<0,05 and it was considered a tendency to 0,1>p>0,05) in order to relate these alterations with IVP efficiency. In relation to cleavage, DCA and DT had a significant negative correlation (p=0,03 and p=0,047, respectively). DB and DBH showed a tendency to a negative correlation (p=0,06 and p=0,07, respectively). In relation to the blastocyst formation, DB showed a tendency to a negative correlation (p=0,09). In addition to this, two abnormality levels were tested in relation to the Heterogeneity (Het) and Decondensation (Des) of chromatin: above 5%, and above 10%. Des presented a significant correlation related to cleavage when used levels above 5% and 10% of decondensation (p=0,03 and p=0,02, respectively), while Het had no significant correlations neither tendencies with the IVP. It was established that the central axis decondensation of the sperm in IVP intensely affects the fertilization process. Other types of alterations may also affects, but with less intensity. DB may affect in blastocyst formation. To evaluate the decondensation, sperm above 5% Des affect the fertilization process. Related to heterogeneity, regardless of the level considered, does not interfere in both parameters evaluated.